Beyond visibility and monumentality : photographic images in the public space : a study for two cases, Terreiro do Paço-Lisbon, Times Square-New York - Mota, João (2016)
This thesis seeks to address the issue of retrieving / adapting the tradition of site-specific large-scale images, (other than images commercially motivated) to contemporary architectural spaces. To achieve this we discussed a conceptual framework to introduce the constitutive and operative concepts of visual public art and spatial politics. Then we made a historical overview of former uses of images in the public arena with special emphasis in the public visual art produced after 1960. Based on those operative concepts, historical framework and on the analytical tools developed during this study, we developed a methodology for designing sitespecific large-scale images in the public space. This methodology is aimed at guiding the production of largescale visual art sensible to the different contexts playing an important role in the becoming of the project, and to incite a sense of placeness on the sites for which large-scale images were proposed. In this study we produced and discussed a group of projects for large-scale images for the squares: Terreiro do Paço – Lisbon and Times Square – New York City. Those projects were guided by the same design method and with the objective of making visible the memory and the contemporaneity of the squares in study. The choice of sites with such different cultural and historical background, was instrumental for understanding the feasibility of a method intended to help the production of large-scale images set in urban environments, sensible and related to complex contexts. The choice of these squares is based on the fact that both squares are unavoidable representations of power (governmental, financial, commercial), a condition that was instrumental in our study for making clear the implications that the history, the public sphere and the public space have on the context and on the actors that have a decisive role in the production of visual art in the public space. The images proposed for the two squares were not confined to photographic images, yet they played a central role. Beyond their instrumental value for the discussion of the method proposed, those projects were concerned with the production of informed commentaries pertinent to the squares in study. To achieve this, the proposed projects made use of their size, monumentally and visibility for the creation of places that stimulate a dwelling experience sensible to the specificity of the place. As a result some projects unveiled new paths/uses for the design of largescale images in the contemporary public space.